MEDICO-SOCIAL STATUS OF COMBUSTIOLOGICAL PATIENTS AND CLINICO-ECONOMIC ANALYSIS OF THE RESULTS OF THEIR TREATMENT - D.G. TATELADZE; S.N. SIMONOV; A.V. GULIN (Avicenna Tajik State Medical University, 2017)
Objective: Analysis of the medico-social status of patients with thermal lesions for assessment of the economic costs of their treatment, the possibility of integration of medical and social technologies, and organization of the combustiological aid on the area of Russian Federation. Methods: The prevalence of thermal damage in 2013-2015 was studied using the example of the combustiological service of the Tambov region of the Russian Federation; the structure of thermal lesions was investigated; the organizational issues of medical and social assistance were considered, and the economic efficiency of regional health resources usage was estimated. The total volume of observations comprised 1264 units. Results: It was shown that thermal trauma possesses regional characteristics. They are determined by the climatic geographic regime of the territory, the tendency of economic development, cultural and national traditions, etc. A constructed model might be used for estimation of the actual costs of a patient's stay in the hospital as well as for their prediction. Various change of expenses such as treatment, anesthesia, examination, specialist services, and surgery determines differences in the overall costs for hospital stay. Conclusion: The developed algorithm for the organization of specialized medical care for victims with thermal injuries allows increasing the efficiency and providing timely assistance to patients of this category as well as rationally planning the economic costs on treatment and rehabilitation.